A case of adoption and allonursing in captive plains zebra (Equus burchellii) - Pluháček, Jan; Bartošová, Jitka; Bartoš, Luděk (Behavioural processes, 2011)
Although allonursing (allowing non-filial offspring to suckle) can be a costly behaviour, it has been reported for many mammals including ungulate species. However, such behaviour is very rare in equids. This is the first report on adoption and allonursing in captive plains zebra (Equus burchellii), recorded in the Dvůr Králové Zoo, Czech Republic. We observed a case of adoption of an orphaned foal by a lactating mare, who then regularly nursed two foals (filial and non-filial). The allonursing mare rejected more suckling attempts, terminated suckling bouts more often, and had a shorter suckling bout duration than other mares. When nursing both foals at the same time, the suckling bout lasted for less time than when nursing a single foal, regardless of whether it was filial or non-filial. The allonursing mare apparently did not discriminate between the filial and non-filial foal.
Keywords: Animals; Female; ženské pohlaví; Aging; kojená zvířata; Maternal Behavior; Data Interpretation, Statistical; Animals, Suckling; Male; adopce; interpretace statistických dat; Adoption; stárnutí; Equidae; mateřské chování; zvířata v ZOO; zvířata; mužské pohlaví; Animals, Zoo